P-2 Effects of warm-up on muscle activity and deep muscle temperature in different sites. (18th November 2016) - Lee, S; Suzuki, T; Hashimoto, J
Abstract : Background: Changes in muscle temperature by warm-up (W-up) depend on the characteristics of the body composition such as fats and muscle activity, and the changes may vary between sites of the body. However, the activity and temperature in specific muscles are not understood, and the scientific evidence of the effectiveness of W-up is necessary. Objective: This study aimed to obtain findings of effective W-up techniques by analysing the activity and changes in the temperature of specified muscles by W-up over time. Method: The subject was a healthy man. We measured the deep muscle temperatures of the vastus medialis muscle (VM), tibialis anterior muscle (TA), biceps femoris muscle (BF), semitendinosus muscle (SM), soleus muscle (SOL), and gastrocnemius muscle (GAS) by using a thermometer (Coretemp CTM-205) and equipped probes. W-up was performed by aerobic exercise for 30 min by using a treadmill and heart rate metre. The deep muscle temperature was measured at 1-minute intervals over time. Muscle activity was measured by using a wireless surface electromyography (EMG) system (WEB-1000) to obtain the mean percent maximal voluntary contraction (%MVC) values and areas at 1-minute intervals. Statistical analyses were performed by using the Tukey's test. The significance level was set at p < 0.05. This study had the approval of the Ethical Committee Aomori University of Health and Welfare. Result: The deep muscle temperature increased from the start to the end of the W-up over time in each muscle. The TA muscle showed the highest temperature (38.14 ± 0.45°C). The significant increases in temperature occurred at 2 min (TA), 3 min (SOL), 4 min (GAS, BF, and SM), and 6 min (VM) after the start of the W-up (p < 0.05, in each). The temperature reached levels that were not significantly different from the highest temperatures of the muscles at 7 min (GAS), 9 min (SOL), 10 min (BF), 11 min (TA), 12 min (SM), and 13 min (VM) after the start of W-up. The%MVC value was significantly higher in the SOL (52.8 ± 5.68%), while it was significantly lower in the TA (25.0 ± 2.17%) than the other muscles (p < 0.01, in each). The mean area on the EMG was significantly larger in the TA (1.786 ± 0.177 mV) but significantly smaller in the SM (1.080 ± 0.149 mV) than in the other muscles (p < 0.01, in each). Discussion: This study demonstrated that changes in the muscle temperature by W-up vary between muscles. The TA muscle showed a significant increase in temperature and highest temperature. In addition, it exhibited the lowest%MVC value and largest area, which is presumably because of the characteristic of the muscle tissue, the high composition of type I myofibers, and the high frequency of use. Furthermore, this study suggests that the increasing pattern in temperature and muscle activity also depended on the difference in muscle activity according to position and muscle mass. Taken together, in order to obtain the effective increase in muscle temperature, individualised W-up techniques should be applied, taking the position and mass of muscles, characteristics of muscle tissues, and frequency of muscle use into account. Acknowledgment: This study was performed with the support of a 2015 research grant from Aomori University of Health and Welfare. References: Lee S, Kanazawa Y, Fukuda M. Comparison between age of the body composition in the limbs as a related factor of conduction heat. J Jpn Soc Balneol Climatol Phys Med 2004 May;65 :165–72. Boström P, Wu J, Jedrychowski MP, Korde A, Ye L, Lo JC, Rasbach KA, Boström EA, Choi JH, Long JZ, Kajimura S, Zingaretti MC, Vind BF, Tu H, Cinti S, Højlund K, Gygi SP, Spiegelman BM. A PGC1-α-dependent myokine that drives brown-fat-like development of white fat and thermogenesis. Nature . 2012 Jan;481 (7382):463–8